Integration of strategy experiential learning in e-module of electronic records management - Sutirman Sutirman; Muhyadi Muhyadi; Herman Dwi Surjono (Jurnal Pendidikan Vokasi, 2017)
This study aims to determine the effectiveness of e-module of electronic records management integrated with experiential learning strategies to improve student achievement in the domain of cognitive, psychomotor, and affective. This study is a research and development. Model research and development used is Web-Based Instructional Design (WBID) developed by Davidson-Shivers and Rasmussen. The steps of research and development carried out by analysis, evaluation planning, concurrent design, implementation, and a summative evaluation. The approach used in this study consisted of qualitative and quantitative approaches. Collecting data used the Delphi technique, observation, documentation studies and tests. Research data analysis used qualitative analysis and quantitative analysis. Testing the effectiveness of the product used a quasi-experimental research design pretest-posttest non-equivalent control group. The results showed that the e-module of electronic records management integrated with experiential learning strategies can improve student achievement in the domain of cognitive, psychomotor, and affective.